2016
DOI: 10.3847/0004-637x/826/2/195
|View full text |Cite
|
Sign up to set email alerts
|

Probability of Cme Impact on Exoplanets Orbiting M Dwarfs and Solar-Like Stars

Abstract: Solar coronal mass ejections (CMEs) produce adverse space weather effects at Earth. Planets in the close habitable zone of magnetically active M dwarfs may experience more extreme space weather than at Earth, including frequent CME impacts leading to atmospheric erosion and leaving the surface exposed to extreme flare activity. Similar erosion may occur for hot Jupiters with close orbits around solar-like stars. We have developed a model, Forecasting a CME's Altered Trajectory (ForeCAT), which predicts a CME's… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 115 publications
0
63
0
Order By: Relevance
“…There are many unknowns here, including the interplanetary magnetic field topology that charged particle trajectories will follow (Parker 1958); the opening angle of the accelerated particles; the planet's cross section, which may be larger than R p 2 p owing to the presence of a magnetosphere; and the direction of the particle ejection with respect to the planet's orbital plane (see Kay et al 2016). A thorough treatment of this issue is beyond the scope of this work.…”
Section: Limitations Of the Methodsmentioning
confidence: 99%
“…There are many unknowns here, including the interplanetary magnetic field topology that charged particle trajectories will follow (Parker 1958); the opening angle of the accelerated particles; the planet's cross section, which may be larger than R p 2 p owing to the presence of a magnetosphere; and the direction of the particle ejection with respect to the planet's orbital plane (see Kay et al 2016). A thorough treatment of this issue is beyond the scope of this work.…”
Section: Limitations Of the Methodsmentioning
confidence: 99%
“…Kay, Opher, & Kornbleuth (2016) found that for typical coronal mass ejection (CME) masses and speeds measured on M dwarfs, the orbiting rocky planets would need magnetic fields between tens to hundreds of Gauss, while hot Jupiters would only require magnitudes between a few and 30 G. The authors concluded that rocky exoplanets possibly could not generate sufficient magnetic field to shield their atmosphere from these eruptions (e.g., Earth exhibits a magnetic field of ≈ 0.5 G). According to Vidotto et al (2013) planetary magnetic fields should be stronger.…”
Section: The Complex Flare Event At Hjd 2457812mentioning
confidence: 99%
“…Planetary magnetic moments may be weakened on tidally-locked M-dwarf planets (Lammer, 2007;Khodachenko et al, 2007). Recent work found that magnetic field strengths of tens to hundreds of Gauss may be required to protect the atmospheres of habitablezone planets orbiting mid M-dwarf stars from coronal mass ejections, or CMEs (Kay et al, 2016). While it could be challenging for rocky exoplanets to attain that strong of a magnetic field, it would likely be easier for similar planets orbiting early M dwarfs to retain their atmospheres, given the lower expected CME impact rates (Kay et al, 2016).…”
Section: Radiative Effectsmentioning
confidence: 99%
“…Recent work found that magnetic field strengths of tens to hundreds of Gauss may be required to protect the atmospheres of habitablezone planets orbiting mid M-dwarf stars from coronal mass ejections, or CMEs (Kay et al, 2016). While it could be challenging for rocky exoplanets to attain that strong of a magnetic field, it would likely be easier for similar planets orbiting early M dwarfs to retain their atmospheres, given the lower expected CME impact rates (Kay et al, 2016). Studies have found that tidally-induced heating of an Earth-mass planet with a fixed, eccentric orbit in the habitable zone of a low-mass star can cause a weakened magnetic field, among other effects, if the tidal heating is strong enough (Driscoll & Barnes, 2015).…”
Section: Radiative Effectsmentioning
confidence: 99%